Evolution of the medical faculty from Tıphane to Cerrahpaşa Medical Faculty (1827–2019) - Dinç, Gülten (Cerrahpaşa Medical Journal, 2020)
Cerrahpaşa Medical Faculty, located in the Fatih district of Istanbul, derives its name from its neighborhood and is the oldest medical faculty in our country besides Istanbul Medical Faculty. The historical origin of the faculty goes back to Tophane-i-Amire, which was established on March 14, 1827. This article summarizes the 192-year history of the faculty as well as its significant transformations during this timeline. Cite this article as: Dinç G. Evolution of the medical faculty from Tıphane to Cerrahpaşa Medical Faculty (1827–2019). Cerrahpaşa Medical Journal 2020; 44(1): 1-20.